(untitled) (International Seven Journal of Multidisciplinary, 2022)
This paper explores the pivotal role of U.S.-based financial advisors in assisting Brazilian companies seeking to expand into the American market. By analyzing key functions such as regulatory compliance, financial structuring, cultural intermediation, and strategic planning, the study highlights the multi-dimensional value of these professionals. Drawing on case studies and academic literature, the paper outlines the challenges Brazilian businesses face and the mechanisms through which financial advisors bridge systemic, legal, and cultural gaps. The findings contribute to the literature on international business, transnational advisory networks, and cross-border financial facilitation.